Phytochemicals and botanical extracts regulate NF-κB and Nrf2/ARE reporter activities in DI TNC1 astrocytes. (July 2016) - Ajit, Deepa; Simonyi, Agnes; Li, Runting; Chen, Zihong; Hannink, Mark; Fritsche, Kevin L.; Mossine, Valeri V.; Smith, Robert E.; Dobbs, Thomas K.; Luo, Rensheng; Folk, William R.; Gu, Zezong; et al.
Abstract: The increase in oxidative stress and inflammatory responses associated with neurodegenerative diseases has drawn considerable attention towards understanding the transcriptional signaling pathways involving NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) and Nrf2 (Nuclear Factor Erythroid 2-like 2). Our recent studies with immortalized murine microglial cells (BV-2) demonstrated effects of botanical polyphenols to inhibit lipopolysaccharide (LPS)-induced nitric oxide (NO) and enhance Nrf2-mediated antioxidant responses (Sun et al., 2015). In this study, an immortalized rat astrocyte (DI TNC1) cell line expressing a luciferase reporter driven by the NF-κB or the Nrf2/Antioxidant Response Element (ARE) promoter was used to assess regulation of these two pathways by phytochemicals such as quercetin, rutin, cyanidin, cyanidin-3-O-glucoside, as well as botanical extracts from Withania somnifera (Ashwagandha), Sutherlandia frutescens (Sutherlandia) and E uterpe oleracea (Açaí). Quercetin effectively inhibited LPS-induced NF-κB reporter activity and stimulated Nrf2/ARE reporter activity in DI TNC1 astrocytes. Cyanidin and the glycosides showed similar effects but only at much higher concentrations. All three botanical extracts effectively inhibited LPS-induced NF-κB reporter activity. These extracts were capable of enhancing ARE activity by themselves and further enhanced ARE activity in the presence of LPS. Quercetin and botanical extracts induced Nrf2 and HO-1 protein expression. Interestingly, Ashwagandha extract was more active in inducing Nrf2 and HO-1 expression in DI TNC1 astrocytes as compared to Sutherlandia and Açaí extracts. In summary, this study demonstrated NF-kB and Nrf2/ARE promoter activities in DI TNC1 astrocytes, and further showed differences in ability for specific botanical polyphenols and extracts to down-regulate LPS-induced NF-kB and up-regulate the NRF2/ARE activities in these cells. Highlights: DI TNC1 astrocytes stably express luciferase reporters for NF-κB or Nrf2/ARE promoter. Phytochemicals down-regulate NF-κB and up-regulate Nrf2/ARE activity. Ashwagandha can effectively stimulate Nrf2 and HO-1 in DI TNC1 astrocytes.